Pitting Potential Improvement of 304 Stainless Steel in Hydrochloric Acid Solution by Terminalia bellirica Fruit Extract - Sutha Sutthiruangwong; Chutikan Wongpaiboon; Nathatida Sritha; Nattha Anukulkich (My University, 2023)
Pitting is a form of localized corrosion. One way to increase pitting resistance is, therefore, to cover surfaces with inhibitor molecules. Many plant extracts have been reported to be able to adsorb onto metal surfaces. According to uniform corrosion, the corrosion rate is reported to be decreased due to adsorption. Terminalia bellirica fruit contains organic chemicals which can adsorb onto metal surfaces. The extract of Terminalia bellirica fruit was used in this work as a corrosion inhibitor for 304 stainless steel in an acidic solution. The results showed a decrease in the corrosion current density of 304 stainless steel when the extract was added. A very high corrosion inhibition efficiency (%IE) of 95% was obtained with an extract addition of 300 mg L–1. Moreover, Terminalia bellirica fruit extract clearly showed an increase in the pitting potential of 304 stainless steel in potentiodynamic polarization curves, which was caused by the physical adsorption. The Langmuir adsorption isotherm model can be used to describe the adsorption of the extract molecule on 304 stainless steel surfaces. Besides the conventional pitting potential (Epit), the parameter called pitting potential improvement in percentage (%PPI) was shown in this work. Additionally, it was calculated based on two boundaries. It can be used to quantify the pitting potential in a percentage. Pitting resistance both in terms of pitting potential and in terms of pitting potential improvement was found to be increased with increasing concentrations of the extract. The highest pitting potential improvement of 29% was achieved at 300 mg L–1 of extraction addition.
Keywords: Pitting Corrosion; Langmuir adsorption model; Hydrochloric acid; Corrosion Behavior and Inhibition